Sex-related differences in the response of anti-platelet drug therapies targeting purinergic signaling pathways in sepsis - Amoafo, Emmanuel Boadi; Entsie, Philomena; Albayati, Samara; Dorsam, Glenn P.; Kunapuli, Satya P.; Kilpatrick, Laurie E.; Liverani, Elisabetta (Frontiers in Immunology, 2022)
Sepsis, a complex clinical syndrome resulting from a serious infection, is a major healthcare problem associated with high mortality. Sex-related differences in the immune response to sepsis have been proposed but the mechanism is still unknown. Purinergic signaling is a sex-specific regulatory mechanism in immune cell physiology. Our studies have shown that blocking the ADP-receptor P2Y12 but not P2Y1 receptor was protective in male mice during sepsis, but not female. We now hypothesize that there are sex-related differences in modulating P2Y12 or P2Y1 signaling pathways during sepsis. Male and female wild-type (WT), P2Y12 knock-out (KO), and P2Y1 KO mice underwent sham surgery or cecal ligation and puncture (CLP) to induce sepsis. The P2Y12 antagonist ticagrelor or the P2Y1 antagonist MRS2279 were administered intra-peritoneally after surgery to septic male and female mice. Blood, lungs and kidneys were collected 24 hours post-surgery. Sepsis-induced changes in platelet activation, secretion and platelet interaction with immune cells were measured by flow cytometry. Neutrophil infiltration in the lung and kidney was determined by a myeloperoxidase (MPO) colorimetric assay kit. Sepsis-induced platelet activation, secretion and aggregate formation were reduced in male CLP P2Y12 KO and in female CLP P2Y1 KO mice compared with their CLP WT counterpart. Sepsis-induced MPO activity was reduced in male CLP P2Y12 KO and CLP P2Y1 KO female mice. CLP males treated with ticagrelor or MRS2279 showed a decrease in sepsis-induced MPO levels in lung and kidneys, aggregate formation, and platelet activation as compared to untreated male CLP mice. There were no differences in platelet activation, aggregate formation, and neutrophil infiltration in lung and kidney between female CLP mice and female CLP mice treated with ticagrelor or MRS2279. In human T lymphocytes, blocking P2Y1 or P2Y12 alters cell growth and secretion in vitro in a sex-dependent manner, supporting the data obtained in mice. In conclusion, targeting purinergic signaling represents a promising therapy for sepsis but drug targeting purinergic signaling is sex-specific and needs to be investigated to determine sex-related targeted therapies in sepsis.